Enhancing Students’ Creative Thinking Through Creative Problem Solving-Based Learning: Design and Implementation - Aulia Ida Zulfitri; Baiq Fatmawati (Journal of Educational Studies, 2026)
This study aimed to develop a Creative Problem Solving-based teaching module and to evaluate its effectiveness in enhancing students’ creative thinking on the topic of viruses in senior high school biology. The study employed a development research design using the 4D model consisting of Define, Design, Develop, and Disseminate stages, followed by a quasi-experimental evaluation in classroom implementation. The participants were tenth-grade students of Madrasah Aliyah Muallimin NWDI Pancor, Indonesia. The experimental group consisted of 33 students, while the control group consisted of 37 students. Data were collected through expert validation sheets, questionnaires, and pretest-posttest assessments. The data were analyzed using descriptive statistics, independent samples t-test, normalized gain analysis, and Cohen’s d effect size analysis. The findings showed that the experimental group achieved greater improvement than the control group. The posttest results indicated a significant difference between the two groups (t = -5.11, p < 0.001), with a large effect size (Cohen’s d = 1.24). These findings suggest that the Creative Problem Solving-based teaching module has promising potential to support students’ creative thinking in biology learning. However, the results should be interpreted within the context of the study setting and research design